Clinical and Histopathological Study on Dog's Tumors in Iraq - Alabbody, Huda. Hameed; Alwan, Mohammed Jwaid; Zenad, Mohummed Mushgil; Wali, Abdulraheem Abduljaleel (Iraqi Journal of Science, 2021)
The study was conducted on twenty dogs from variety breeds to estimate theincidence of tumor mass and determine the risk factors of survey to cases of a yearin veterinary hospital in Baghdad. The most common clinical signs were, ulceration,bleeding into lesions in addition to drowsiness, anorexia, fever and the others weredepended tumor's location in dog's body like lameness, lacrimation and bloodyconstipation etc.The results showed 70% of the infected dogs were working with military forcesand 30% of them were pet dogs and we found that the highest percentage of tumoraccrued in dogs aged more than 10 years and the females recorded 60% of infection.Terrier breed had the highest percentage of infection (30%) followed by Germanshepherd (25%). the most tumor affected part of the body were mammary glands infemales and the limbs in both gender (25% each one) and followed by the othersites, the histopathology picture had recorded seven types of malignant tumors in(skin, intestine and mammary glands) more frequent was Sequmas cell carcinoma35% Adenocarcinoma 20%. Some dogs had more than one type of cancer, and somecases had recorded of benign tumors other cases had only transformed tissue but notcancer.